Assessment of Grassland Ecosystem Services and Analysis on Its Driving Factors: A Case Study in Hulunbuir Grassland - Li, Minhuan; Wang, Xiaoyu; Chen, Jiancheng (Frontiers in Ecology and Evolution, 2022)
Grassland is the largest terrestrial ecosystem in China, and its ecological environment is currently facing severe challenges. Scientific and effective grassland ecosystem service assessment and in-depth analysis of its change mechanism are of great significance to clarify its protection demand and spatial optimization layout. This study used a set of quantitative surrogate biophysical indicators to evaluate the capability of grassland ecosystem services (carbon fixation, soil protection, water purification and provision, biodiversity conservation) in the Hulunbuir grassland from 2000 to 2015 and use econometric models to explore their dynamic change mechanism. The results showed that, from 2009 to 2012, the grassland ecosystem service value significantly declined, and from 2013 to 2015, its value significantly improved, but the overall level was still lower than that of 2000. The factor that has the highest degree of impact on grassland ecosystem services is the soil potassium content, and there is a significant positive correlation. This is mainly due to the important role of potassium in the photosynthesis of grassland plants; the least influential factors are social economic factors such as population and GDP. It shows that the sparsely populated grassland ecosystem is not sensitive to these factors. In addition, climate, topography and grassland management policies all have a significant impact on grassland ecosystem services. Against the backdrop of intensified pressure on ecological grassland protection and a surging market demand for livestock products based on grassland resource input, the sustainable development of grassland areas needs to improve the supply capacity of grassland while ensuring its ecological security, so as to realize a win–win situation for its ecological and production functions.